Risk Factors for Sepsis Based on Sepsis-3 Criteria after Orthotopic Liver Transplantation - Yanling Wang; Yu Gu; Fei Huang; Dezhao Liu; Zheng Zhang; Niman Zhou; Jiani Liang; Changyin Lu; Dongdong Yuan; Ziqing Hei (Mediators of Inflammation)
Sepsis is a common complication of solid organ transplant procedures and, in particular, can affect the prognosis of orthotopic liver transplantation (OLT). This retrospective study determined the pre-, peri-, and postoperative risk factors for sepsis after OLT, using as reference the 2016 Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3). Pre-, peri-, and postoperative clinical data of the sepsis-positive (n=85) and sepsis-negative (n=41) groups were analyzed for potential risk factors of OLT-related sepsis. The sepsis-positive patients had a significantly higher rate of dialysis (49.4%), longer time under mechanical ventilation (1.5 d), higher hospitalization costs (0.41 million RMB), and worse survival rate (68.5%), compared with the sepsis-negative patients (4.8%, 1 d, 0.30 million RMB, and 73.1%, resp.). The multivariate logistic analysis identified the following as risk factors for OLT-related sepsis: preoperative Child-Pugh grade C (OR 10.43; 95% CI 2.081–52.292; P=0.004), preoperative hypercalcemia (OR 6.372; 95% CI 1.693–23.98; P=0.006), and perioperative acidosis (OR 6.364; 95% CI 1.196–33.869; P=0.030). Patients with preoperative Child-Pugh grade C, preoperative hypercalcemia, or perioperative acidosis are at higher risk for developing sepsis after OLT. When any of these problems occur, timely sepsis management should be planned.